Reuse: aplicativo sobre reciclagem - OLIVEIRA, Ayssa Azevedo de; DEL VALLE, Barbara; FERREIRA, Iagho da Cunha; PINHEIRO, Mateus Simplício; GONÇALVES, Melissa da Silva (172, 2025)
Este trabalho aborda o desenvolvimento de um protótipo de aplicativo móvel para combater o baixo índice de reciclagem no Brasil, onde apenas 4% dos resíduos sólidos urbanos são reaproveitados. Em resposta ao descarte incorreto e à falta de informação, o aplicativo visa educar e orientar sobre a separação correta dos materiais. Alinhado aos Objetivos de Desenvolvimento Sustentável (ODS 12 e 13), o projeto utiliza tecnologia para promover conscientização e engajamento, esperando reduzir erros e aumentar a eficiência da reciclagem. A metodologia envolveu pesquisa e a criação de uma ferramenta interativa com geolocalização e gamificação, com o intuito de facilitar a adesão a práticas mais sustentáveis.

This work presents the prototype of a mobile application designed to guide and assist in recycling, addressing the critical issue of improper solid waste disposal. Faced with the alarming fact that only 4% of the 80 million tons of urban solid waste annually produced in Brazil are effectively recycled, this application aims to provide clear, objective, and educational information on correct waste separation. Aligned with SDGs 12 and 13, the project utilizes mobile technology to promote environmental awareness and behavioral change. The methodology involved comprehensive bibliographic research and the development of a functional prototype, incorporating features such as geolocation for collection points and gamification for user engagement. This initiative seeks to bridge knowledge gaps and enhance recycling practices, contributing to more sustainable waste management and a greener future.
Keywords: Gestão de resíduos; Reciclagem; Informação e Comunicação